Answer: x = 0; y = 2; z = 5
Step-by-step explanation:
x+2y+z=9
x-y+3z=13
2z=10
==
Start with the last equation: 2z = 10, therefore z = 5 [easy]
Let's rewrite the second equation with 1) z=5, and 2) rearrange to find x:
x-y+3z = 13
x - y +3*5 = 13
x = y-2
Now use the values for x [(y-2)] and y [5] in the first equation:
X+2y+z=9
(y-2) +2y + 5 = 9
3y +3 = 9
3y = 6
y = 2
Now that we have y [2] and z [5], let's use the first equation to solve for x:
x+2y+z=9
x + 4 + 5 = 9
x + 9 = 9
x = 0
====
Try the three values (x=0, y=2, and z=5) in any of the formulas. The result should/will equal the number shown.
Answer:
- The term observed frequencies are found in the sample.
Hence, option 'd' is correct.
Step-by-step explanation:
Unlike the expected frequency which is obtained based on prediction, the observed frequency is the actual frequency that is determined from the experiment.
Therefore, we conclude that
- The term observed frequencies are found in the sample.
Hence, option 'd' is correct.
Answer:
L = 48
Step-by-step explanation:
Given that L varies directly with Z² , then the equation relating them is
L = kZ² ← k is the constant of variation
To find k use the condition L = 12 when Z = 2 , then
12 = k × 2² = 4k ( divide both sides by 4 )
3 = k
L = 3Z² ← equation of variation
When Z = 4 , then
L = 3 × 4² = 3 × 16 = 48
Answer:
0.63636363636
Step-by-step explanation:
hope that kinda helped (if the answer is wrong please tell me)